1987
DOI: 10.1002/j.1551-8833.1987.tb02828.x
|View full text |Cite
|
Sign up to set email alerts
|

The Transfer of Radon From Domestic Water to Indoor Air

Abstract: Theoretical and experimental literature dealing with the release of radon from water to air is reviewed and synthesized. Primary emphasis is placed on releases from domestic water supplies to indoor air within the context of a general indoor radon problem. The widely used assumption of 1 pCi/L increment in indoor air per 10 000 pCi/L in the water supply is valid, but regional and individual variations are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…7). Groundwater within the Peters Creek Schist (Xpc) has a radon concentration range of 1,743 to 9,135 pCi/L, which corresponds to estimated contributions to indoor air of 0.2 to 0.9 pCi/L, based on exchange ratios of 10,000:1 for water:air developed by Prichard (1987). Although the magnitude of these contributions from the groundwater is relatively low, 81 percent (table 4) of the population living on the Peters Creek Schist outcrop relies on groundwater supplied by domestic self-supply wells.…”
Section: Classification Of Potential Radon Exposure From Groundwater mentioning
confidence: 99%
See 1 more Smart Citation
“…7). Groundwater within the Peters Creek Schist (Xpc) has a radon concentration range of 1,743 to 9,135 pCi/L, which corresponds to estimated contributions to indoor air of 0.2 to 0.9 pCi/L, based on exchange ratios of 10,000:1 for water:air developed by Prichard (1987). Although the magnitude of these contributions from the groundwater is relatively low, 81 percent (table 4) of the population living on the Peters Creek Schist outcrop relies on groundwater supplied by domestic self-supply wells.…”
Section: Classification Of Potential Radon Exposure From Groundwater mentioning
confidence: 99%
“…The limits proposed by the EPA do not apply to drinking water obtained from domestic self-supply wells, and the relative contribution of radon from groundwater to indoor air is not known, although each 10,000 pCi/L in water has been estimated to increase indoor air concentrations by 1 pCi/L and thus increase health risks (Milry and Cothern, 1990;Prichard, 1987). The 10,000:1 water:air radon ratio varies considerably from house to house and is a general national average (National Research Council, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main agents of this exposition is 222 Rn, especially if concentrated in poorly aerated dwellings. While most of the radon present in indoor environments is originated in the soil, the use of groundwater can represent, depending of local conditions, a significant mechanism of radon transfer to indoor air (Gessel and Prichard, 1978;Cothern et al, 1986;Prichard, 1987;Lawrence et al, 1992;Folger et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, starting with reports of Kahlos and Asikainen (1980), have suggested that radon dissolved in the home water supply can substantially contribute to the indoor radon of the home. Several subsequent studies have estimated that a water supply with a radon concentration of 10,000 pCi/L would add about 1 pCi/L to the indoor radon due to the outgassing of the domestic water supply (Cothern, 1987;Prichard, 1987). Three booklets published by the EPA (US-EPA 1987a, 1987b, 1987c state that radon-enriched domestic water must have about 10,000 pCi/L of radon to contribute 1 pCi/L to indoor radon (a 10,000:1 ratio).…”
Section: Introductionmentioning
confidence: 99%